E-module Newton's Law of Gravity based Guided Inquiry to Train Critical Thinking Skills - Sari, Deswita Elliya; Herlina, Kartini; Viyanti, Viyanti; Andra, Doni; Safitri, Ida (Faculty of Science and Education, UIN Walisongo Semarang, 2023)
The study aims to develop an electronic module based on guided inquiry on Newton's law of gravity material that is valid, practical, and effective. The developed e-module aims to practice critical thinking skills in physics learning. This development research uses the ADDIE development method which consists of five steps, namely analysis, design, development, implementation, and evaluation. Student response questionnaires to guided inquiry e-modules and tests of critical thinking skills became research instruments. Data analysis presented with quantitative descriptive. The product validity was assessed by 3 experts with an average score of 3.63 with category very valid. The practicality of the product consisted of readability which was tested on 15 high school students in Grade X and the teacher's perception of the suitability of guided inquiry-based learning activities in e-modules by obtaining an average percentage of 90% in the category very practical. The effectiveness of the product is assessed based on students' responses of critical thinking skills are improve after using the e-module by obtaining a product effectiveness percentage of 87% with category very effective. Student response questionnaire showed a positive response to the developed e-module. Based on the analysis of the research results, it is stated that the guided inquiry-based e-module on Newton's law of gravity is valid, practical, and effective for practicing critical thinking skills.